Stabilization with Exchange Rate Management - Drazen, Allan; Helpman, Elhanan (Quarterly Journal of Economics, 1987)
Stabilization programs in open economies typically consist of two stages. In the first stage the rate of currency devaluation is reduced, but the fiscal adjustment does not eliminate the fiscal deficit that causes growth of debt and loss of reserves, making a future policy change necessary. Only later, at a second stage, is this followed by either an abandonment of exchange rate management or by a sufficiently large cut in the fiscal deficit. We study how different second-stage policy changes affect economic dynamics during the first stage. These changes include tax increases, budget cuts on traded and nontraded goods, and increases in the growth rate of money.